2021
DOI: 10.3390/en14082184
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Wavelet Transform for the Real-Time Smoothing of Wind Turbine Power Using Li-Ion Batteries

Abstract: Energy Storage Systems (EES) are key to further increase the penetration in energy grids of intermittent renewable energy sources, such as wind, by smoothing out power fluctuations. In order this to be economically feasible; however, the ESS need to be sized correctly and managed efficiently. In the study, the use of discrete wavelet transform (Daubechies Db4) to decompose the power output of utility-scale wind turbines into high and low-frequency components, with the objective of smoothing wind turbine power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…It is then apparent that the optimization of the level of decomposition plays an important role to correctly define the power content to be split between the BESS and the grid. Previous experience showed that for the Daubechies family, often used in this kind of applications, moderate decomposition levels (2-3) are sufficient to guarantee a good smoothing of wind power values [6], as shown in Figure 3 and Figure 4.…”
Section: Wavelet Decomposition Levelmentioning
confidence: 98%
See 3 more Smart Citations
“…It is then apparent that the optimization of the level of decomposition plays an important role to correctly define the power content to be split between the BESS and the grid. Previous experience showed that for the Daubechies family, often used in this kind of applications, moderate decomposition levels (2-3) are sufficient to guarantee a good smoothing of wind power values [6], as shown in Figure 3 and Figure 4.…”
Section: Wavelet Decomposition Levelmentioning
confidence: 98%
“…The algorithm can work in real-time mode or in offline, and its main settings are reported in Table 1. For additional info, the readers can refer to [6]. Table 1.…”
Section: Power Smoothing Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…The battery model simulates the behaviour of a lithium-ion Battery Energy Storage System (BESS) and is based on a previous study by some of the authors [21]. The main considered parameters are the state of charge (SOC), limited to 15-95% to avoid harmful deep cycles, and the charging rate (C-rate), limited to full charge in 1 hour (1C) and full discharge in 2 hours (2C).…”
Section: Batterymentioning
confidence: 99%